The Impact of Perceived Price towards Perceived Value Through the Mediation of Perceived Quality: A Case of Brand X Smartphone in Indonesian Middle-Class Customers - Ikaningrum Shintaputri; Amelinda Jane Wuisan (iBuss Management, 2017)
To grab the opportunity in the smartphone industry, companies can increase customer’s perceived value by increasing its product’s benefits (quality) or reducing its product’s costs (price). Scholars argue that reducing perceived price could increase perceived value but also reduce perceived quality. This is because perceived quality may mediate the relationship between perceived price and perceived value. Therefore, this research’s objective is to understand the mediation effect in perceived price and perceived value relationship in smartphone industry.This research has collected the data from 70 respondents in Indonesia. The data has passed validity & reliability test and processed using multiple regression analysis with Sobel test. The result of this research finds an insignificant relationship between perceive price and perceived value and a significant relationship between perceived price and perceived quality. Thus, there is no mediation of perceived quality in the relationship between perceived price and perceived value. Furthermore, this research finds a significant relationship between perceived quality and perceived value. Keywords: Perceived price, perceived quality, perceived value, smartphone industry